It's not "Just poverty": Educational, social, and economic functioning among young adults exposed to childhood neglect, abuse, and poverty. (March 2020) - Font, Sarah A.; Maguire-Jack, Kathryn
Abstract: Background: Neglect is the most common allegation in Child Protective Services (CPS) investigations. Researchers and media have questioned whether and how CPS-investigated neglect differs from poverty. Prior studies are limited by self-reported or cross-sectional measures, small samples, and short observation periods. Objective: (1) To estimate the "added harm" of CPS-investigated neglect, net of poverty exposure (depth and duration), on high school completion, employment and earnings, incarceration, and teen parenthood; (2) To assess whether abuse is a stronger risk factor for adverse outcomes than neglect. Participants and Setting: 29, 154 individuals born in 1993–1996 from Milwaukee County, WI, who either received food assistance or were reported to CPS before age 16. Method: Using logistic regression with a rich set of social and demographic controls, we compared individuals with CPS-investigated neglect, abuse, or both abuse and neglect in early childhood or adolescence to those who experienced poverty but not CPS involvement. We calculated cumulative measures of poverty duration and poverty depth between ages 0 and 16 for the full sample using public benefit records. Results: Outcomes among children with alleged or confirmed neglect were statistically significantly worse in all domains than impoverished children without maltreatment allegations, and similar to children with alleged or confirmed abuse. Effect sizes varied by outcome. Conclusions: Overall, this study suggests that CPS allegations of neglect are distinct from poverty and an important risk factor for adverse outcomes in adulthood.